Anti-TNF Therapy and the Risk of Cancer and Infection in Pakistani Rheumatoid Arthritis Patients: A Case-Control Study - SHAHID, MUHAMMAD NAUMAN SHAHID; FAYAZ, MIAN SARMAD FAYAZ; ANAM, AREESHA ANAM; FAROOQ, UMER FAROOQ; SALEEM, HAMZA SALEEM; HASSAN, MUHAMMAD SAMI UL HASSAN; RAZZAQ, MISHAAL RAZZAQ (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Rheumatoid arthritis functions as a persistent autoimmune condition which creates major consequences for patient lifestyle quality. TNF inhibitor medications (anti-TNF therapy) have transformed RA treatment by lowering inflammation yet medical practitioners still worry about their ability to enhance infection and cancer risks. Aim: To evaluate the risk of infection and malignancy in rheumatoid arthritis (RA) patients undergoing anti-TNF therapy, comparing them with those receiving conventional treatment. Methods: A total of 500 RA patients, aged 20-50 years, were recruited from multiple tertiary care hospitals in Lahore, Pakistan. The cohort was divided into two groups: Group A (Non-Biologic, n=250) and Group B (Biologic, n=250). Demographic data, lifestyle factors, disease duration, and biomarkers including CRP, IL-6, TNF-α, PCT, serum ferritin, immunoglobulin levels, RF, and ACPA were measured. Statistical analyses, including descriptive statistics, t-tests, and logistic regression, were performed. Kaplan-Meier survival analysis was conducted to assess long-term patient outcomes. Results: The Biologic Group showed significantly reduced levels of inflammatory markers (CRP, IL-6, TNF-α) compared to the Non-Biologic Group, indicating better disease control. Elevated immunoglobulin levels (IgG, IgA) in the Biologic Group suggested immune modulation. While infection rates were comparable between both groups, the Biologic Group showed a lower risk of severe disease progression. The Kaplan-Meier survival analysis indicated a statistically significant survival advantage for the Biologic Group (χ² = 5.67, p = 0.017). Conclusion: Anti-TNF therapy effectively reduces inflammation and improves clinical outcomes in RA patients without introducing significant new health risks. However, regular monitoring for infections and malignancies, especially non-melanoma skin cancers, is essential to optimize long-term safety. The study highlights the therapeutic benefit of biologics while emphasizing the need for tailored patient care and continuous surveillance.